The Effect of Multi-Dimensional Organizational Justice on Nurse Empathy in Islamic Religious Care Services During the Covid-19 Pandemic in Hospital - Basirun Basirun; Putra Agina Widyaswara Suwaryo; Yuli Susilowati; Rosmawati Rosmawati; Umi Aminatul Qirom (GLOBAL HEALTH SCIENCE GROUP, 2022)
Nursing policy makers should read this research because nurses' empathy in patient care is strongly influenced by many factors, including organizational justice. Several previous research results have carried out this research. Even so, a firm answer is needed about whether empathy is influenced by organizational justice more comprehensively in its dimensions. Objective to determine the effect of multidimensional organizational justice on nurse empathy. This study uses a quantitative survey research method with a cross-sectional study approach with a sample of 126 nurse respondents. The sample used is purposive sampling. Data analysis used Structural Equation Modeling SEM AMOS 22.00. The results of the analysis p = 0.026, accepted, meaning that the procedural justice variable has a significant effect on empathy. The results of the analysis obtained that the value of p = 0.033, n is accepted, meaning that the Distributive Justice variable has a significant effect on empathy. The results of the analysis obtained the p*** value, accepted, meaning that the Interpersonal Justice variable had a significant effect on empathy. 4) The results of the analysis obtained that the value of p = 0.8 was rejected, meaning that there was no influence of Informational Justice on Empathy. Three dimensions of justice have an effect on empathy while informational justice has no effect on empathy